2018
DOI: 10.1155/2018/5804687
|View full text |Cite
|
Sign up to set email alerts
|

A Revised Version of Diabetes Quality of Life Instrument Maintaining Domains for Satisfaction, Impact, and Worry

Abstract: Background Diabetes quality of life (DQoL) instrument has been widely used to measure quality of life among diabetes patients. This study aimed to develop a revised version of DQoL instrument that incorporated issues of redundancies in the items and strengthen the basis of validity of the instrument. Methods This was a cross-sectional study where diabetes patients were recruited from December 1, 2014, until end of March 2015 at a public health clinic in Peninsular Malaysia. A questionnaire that included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…The results of the Arabic version were also compared with the Malaysian version of the DQoL questionnaire (16). The result of the present study resembled the 3-factor model of the Malaysian version, which consists only of 18 items, as more items were dropped that were identified as duplications, including (I14) "How often do you find yourself explaining what it means to have diabetes?…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The results of the Arabic version were also compared with the Malaysian version of the DQoL questionnaire (16). The result of the present study resembled the 3-factor model of the Malaysian version, which consists only of 18 items, as more items were dropped that were identified as duplications, including (I14) "How often do you find yourself explaining what it means to have diabetes?…”
Section: Discussionmentioning
confidence: 59%
“…The only item that remained from the original vocational/social worry scale was W7, which was loaded in the new worry scale. A previous study had also reported a large amount of missing data in these items as they did not apply to many of the respondents (16). The new formulated Worry scale comprised 4 items that were converted from dichotomous questions to 5-Likert scale questions to be more suitable for EFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semakin tinggi nilai hasil kuesioner yang didapatkan maka semakin tinggi kualitas hidup pasien tersebut. Penelitian Bujang dkk., tahun 2018 menilai reliabilitas masing-masing domain adalah 0,92 (satisfaction), 0,78 (impact) dan 0,79 (worry) dengan nilai alfa ≥ 0.70 dan merupakan kuisioner yang valid (16).…”
Section: Kualitas Hidupunclassified
“…In spite of being recommended for patients with CV and renal disease, SGLT-2i are currently under prescribed, and when they are prescribed they're being prescribed to the patients who are not likely to benefit the most. 7,8 The current review aimed to assess the mechanisms of action of dapagliflozin and its effects on HHF and MACE.…”
Section: -5mentioning
confidence: 99%